A new combination in Lepidoziaceae (Marchantiophyta) - Sass-Gyarmati, Andrea; Pócs, Tamás (Phytotaxa, 2019)
The format of this note follows Söderström et al. (2012). One name is validated here. Bazzania lacouturei (Steph.) Gyarmati, comb. nov. Basionym:—Mastigobryum lacouturei (Stephani 1924: 471). Type:—MADAGASCAR. Betsileo, Villaume 275 (G-00045391 holotype!). ≡ Bazzania lacouturei (Stephani) (Arnell 1965: 66), nom. inval. (ICN Art. 41.5; basionym and its place of valid publication is not cited). Note:—This species is missing from the World Checklist (Söderström et al. 2016) and it was referred to the Bazzania decrescens complex by Jones (1975). The latter opinion is insupportable, as no underleaves are connate with the side leaves.